Descrição das tempestades observada por meio dos dados do radar meteorológico de Belém-PA, utilizando a rotina TrackGridStat através do software livre Titan - PACHECO, Nathalia Farias (2019)
Belém - Pa located at latitude 01 ° 26 ' S and longitude 48 ° 29' W with an area of 1,070 km2 , has a weather radar operating in monitoring mode with radius of 240 km of accuracy . This paper analyzed characteristics of the storms that occurred in the area surrounding the meteorological radar of Bethlehem - Pa SIPAM using the data from the months of April and October 2010. TITAN software was used by TrackGridStat routine for the extraction of information from cells storm , obtaining the characteristics of height, reflectivity ( dBz ) , top, bottom , travel speed and time of occurrence of rain. A large concentration of convection and availability of severe storms for the month of October, which was also found maximum tops reaching 26 km in height was observed ; In April maximum cloud top up to 21 km was observed . In the analysis of reflectivity maxima of 54 dBz for the rainy month of April and maximum values of 65 dBz considered dry month in October found. The magnitude represented the variation of reflectivity demonstrates the behavior of the systems operating in the region as major systems and the interaction between mesoscale phenomena such as the Intertropical Convergence Zone , squall lines , Cyclonic Vortex high levels (which acts on the northeast ) , Bolivian High , wave disturbances and east breezes which were primarily responsible for the formation of storms during the rainy season in the region . However , the two months showed different characteristics in their behavior in the evolution of storms . With the results we have a broader " vision " of the characteristics of the storm in the Amazon region , using radar tool that will add value in understanding these patterns of precipitation in the region for future studies of storms in the northern region .